2007
DOI: 10.1007/s10152-007-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton vertical distribution and migration off Central Peru in relation to the oxygen minimum layer

Abstract: Vertical distribution and diel vertical migration of a zooplankton community were studied at two stations oV Central Peru in April 2006. Zooplankton was collected at Wve depth strata by vertical hauls with Hydo-Bios multinet (300-m mesh, 0.25-m 2 mouth size). The zooplankton community was distributed in relation to a strong, shallow oxycline (1 ml l ¡1 oxygen isopleth generally above 36 m). The highest total abundance was always in the upper, welloxygenated layer. The most important species were: Acartia tonsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…First, H. digitata may be positioned to maximize encounters and capture of copepods and other prey. The habitat depth of H. digitata approximately coincides with a peak in mesopelagic biomass (Saltzman and Wishner 1997a,b;Criales-Hernandez et al 2008) and, specifically, in mesopelagic calanoid copepods (Mauchline 1998). In feeding experiments and observations, omnivorous and carnivorous planktonic foraminifera have been shown to prey predominantly on copepods, in keeping with the copepods' relatively high abundance Caron and Be 1984;Swanberg and Caron 1991), and to prefer calanoid copepods over other copepod taxa (Spindler et al 1984).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, H. digitata may be positioned to maximize encounters and capture of copepods and other prey. The habitat depth of H. digitata approximately coincides with a peak in mesopelagic biomass (Saltzman and Wishner 1997a,b;Criales-Hernandez et al 2008) and, specifically, in mesopelagic calanoid copepods (Mauchline 1998). In feeding experiments and observations, omnivorous and carnivorous planktonic foraminifera have been shown to prey predominantly on copepods, in keeping with the copepods' relatively high abundance Caron and Be 1984;Swanberg and Caron 1991), and to prefer calanoid copepods over other copepod taxa (Spindler et al 1984).…”
Section: Discussionmentioning
confidence: 97%
“…While calanoid abundances decrease with water depth, they are generally abundant in the upper 300 m and decrease irregularly to 1000 m (Mauchline 1998). In Monterey Bay, a , 300-m habitat depth likely coincides with a peak in mesopelagic biomass above the oxygen minimum zone (Saltzman and Wishner 1997a,b;Criales-Hernandez et al 2008), a peak in mesopelagic copepod abundance (Childress 1977;Thuesen et al 1998), the diel ambits of vertically migrating copepods (Huntley and Brooks 1982;Hattori 1989), deep ontogenetic or seasonal phases of the dominant epipelagic copepods like Calanus pacificus or Metridia pacifica (Batchelder 1985;Ohman et al 1998;Johnson and Checkley 2004), and the margin between the lower edge of the California Current and the upper extent of the California Undercurrent.…”
Section: Discussionmentioning
confidence: 99%
“…by Levin & Edesa (1997) and the spionid Paraprionospio pinnata by González & Quiñones (2000). Responses to the physiological constraints of OMZs have also been documented in several species of calanoid copepods via ontogenetic zonation (Wishner et al 2000, Loick et al 2005, Criales-Hernandez et al 2008.…”
Section: Introductionmentioning
confidence: 93%
“…The zooplankton distribution throughout the water column displays different patterns of vertical structure for a variety of groups (Criales-Hernández et al 2008). Field and theoretical studies suggested that this heterogeneous use of space can be mainly attributed to physical processes, seasonal, ontogenetic or diel vertical migrations, body size, morphologies, feeding resources, reproductive success, predation risk and/or competitive abilities (Jeffries and Lawton 1984;Fossheim and Primicerio 2008;Marrari et al 2011;Sato et al 2011).…”
Section: Introductionmentioning
confidence: 99%